Intelligent Image Capturing Alarm System Using Raspberry Pi - Mohd Annuar, Khalil Azha; Ab Hadi, Nik Azran; Subramaniam, Siva Kumar; Mohd Ab Halim, Mohd Firdaus; Nor Shah, Mohd Badril; Kadmin, Ahmad Fauzan; Mohd Noh, Mohd Syahrin Amri; Abdul Salam, Azuki (Universitas Ahmad Dahlan (UAD), 2017)
Home surveillance system assumes an essential part in this present day living style to help recognizing illegal activities. In this proposed paper, an intelligent image capturing alarm system to protect locker was developed. Raspberry Pi 2 is used as the main controller (server). At the point when any conceivable intrusion is identified, a webcam installed to Raspberry Pi 2 will capture the picture of the intruder. In the meantime, the spotlight or light of the house which represented by an LED will be turned "ON" alongside an alarm sound from a buzzer which is fixed as an output. Taking everything into account, this improvement offers reasonable and easy to use surveillance alarm system.